Autologous protein solution prepared from the blood of osteoarthritic patients contains an enhanced profile of anti‐inflammatory cytokines and anabolic growth factors. Issue 10 (1st July 2014) - O'Shaughnessey, Krista; Matuska, Andrea; Hoeppner, Jacy; Farr, Jack; Klaassen, Mark; Kaeding, Christopher; Lattermann, Christian; King, William; Woodell‐May, Jennifer
ABSTRACT The objective of this clinical study was to test if blood from osteoarthritis (OA) patients (n = 105) could be processed by a device system to form an autologous protein solution (APS) with preferentially increased concentrations of anti‐inflammatory cytokines compared to inflammatory cytokines. To address this objective, APS was prepared from patients exhibiting radiographic evidence of knee OA. Patient metrics were collected including: demographic information, medical history, medication records, and Knee Injury and Osteoarthritis Outcome Score (KOOS) surveys. Cytokine and growth factor concentrations in whole blood and APS were measured using enzyme‐linked immunosorbent assays. Statistical analyses were used to identify relationships between OA patient metrics and cytokines. The results of this study indicated that anti‐inflammatory cytokines were preferentially increased compared to inflammatory cytokines in APS from 98% of OA patients. APS contained high concentrations of anti‐inflammatory proteins including 39, 000 ± 20, 000 pg/ml IL‐1ra, 21, 000 ± 5, 000 pg/ml sIL‐1RII, 2, 100 ± 570 pg/ml sTNF‐RI, and 4, 200 ± 1, 500 pg/ml sTNF‐RII. Analysis of the 82 patient metrics indicated that no single patient metric was strongly correlated (R2 > 0.7) with the key cytokine concentrations in APS. Therefore, APS can be prepared from a broad range of OA patients. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1349–1355, 2014.